2023
DOI: 10.3389/fcimb.2023.1130483
|View full text |Cite
|
Sign up to set email alerts
|

The value of next-generation metagenomic sequencing in pathogen detection of pleural effusions and ascites from children with sepsis

Abstract: ObjectiveTo investigate the diagnostic value of metagenomic next-generation sequencing (mNGS) using pleural effusion and ascites from children with sepsis.MethodsIn this study, children with sepsis or severe sepsis and appeared pleural or peritoneal effusions were enrolled, of whom the pleural effusions or ascites and blood samples were conducted pathogen detection using both conventional and mNGS methods. The samples were divided into pathogen-consistent and pathogen-inconsistent groups based on the consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…As for clinically relevant bacteria, the top 3 frequently detected species were Klebsiella pneumoniae , E. coli and Staphylococcus aureus , from sterile body sites, while Mycobacterium tuberculosis , E. coli and Pseudomonas aeruginosa , from microbial-colonized sites. These species were in line with the results of several previous studies that investigated pathogens detected from plasma ( Eichenberger et al., 2022 ), SCE ( Liu et al., 2023 ), abscess ( Zhao et al., 2021 ) and respiratory tract ( Jin et al., 2022 ). Among the above species, there was a high concordance in detection of E. coli , P. aeruginosa and S. aureus between NST and culture.…”
Section: Discussionsupporting
confidence: 91%
“…As for clinically relevant bacteria, the top 3 frequently detected species were Klebsiella pneumoniae , E. coli and Staphylococcus aureus , from sterile body sites, while Mycobacterium tuberculosis , E. coli and Pseudomonas aeruginosa , from microbial-colonized sites. These species were in line with the results of several previous studies that investigated pathogens detected from plasma ( Eichenberger et al., 2022 ), SCE ( Liu et al., 2023 ), abscess ( Zhao et al., 2021 ) and respiratory tract ( Jin et al., 2022 ). Among the above species, there was a high concordance in detection of E. coli , P. aeruginosa and S. aureus between NST and culture.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, metagenomics and bacterial metataxonomics unveiled greater microbial heterogeneity than could be detected by conventional culture. Similar to recent work 16,19 , we observed that polymicrobial bacterial infection was also occasionally associated with fungal coinfection (albeit in very low abundance) using metagenomics, confirming the challenging nature of diagnosing and treating complex polymicrobial pleural infections across microbial domains. Streptococcal and staphylococcal phages were also seen in five cases of pleural infection, with their host species not always detected, suggesting possible lytic activity towards their host within the pleural space, or incidental phage transit from other body sites 30 .…”
Section: Discussionsupporting
confidence: 88%
“…Clinical decision-making in suspected pleural infection is challenging due to low culture positivity rates 58 , resulting in frequent diagnostic uncertainty and antimicrobial overuse. Recent work 7,8,15,16,19 has highlighted potential advantages of molecular methods for diagnosing and determining the aetiology of pleural infection. Our pilot feasibility study adds to this growing body of work, being one of the first studies to apply shotgun metagenomics on pleural infections, and the first to prospectively collect and profile consecutive pleural fluid specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations